Absence of a Power of Attorney to Appear before a Notary in Making the Deed of Statement of Resolutions of the Extraordinary General Meeting of Shareholders - Bellatric Andini Putri; Tjhong Sendrawan (Faculty of Law, Universitas Pekalongan, 2022)
The background of this research is the absence of a power of attorney to appear before a notary as the basis for the authority of the appearer in making the Deed of Resolutions of Extraordinary General Meeting of Shareholders (PKR deed). The problems studied in this research are the reasons why a power of attorney to appear before a notary is needed in the process of making a PKR deed and efforts that can be made by a notary so that the deed he makes still complies with statutory provions, if the power of attorney does not exist. The research was conducted using a literature study with an analytical descriptive research typology by examining secondary data in the form of primary and secondary materials. Primary legal materials consist of the Civil Code, Notary Office Law, and Limited Liability Company Law, while secondary legal materials consist of books, journals, articles, and internet media related to Limited Liability Companies, the role of a Notary in making the deeds of Limited Liability Companies, and notary’s obligations in making authentic deeds. The results of this study explain that a power attorney with the right of substitution for a appearer who wants to appear before a Notary to state the contents of a meeting decision in a PKR deed is important. With the existence of a power of attorney, the appearer as the proxy holder has the authority to act to represent the interests of other shareholders present at the EGMS. Conversely, if there is no power of attorney, then the appearer does not have the authority to act. The result of the incompleteness of the power of attorney for the appearer in making the PKR deed is that the PKR deed can be canceled because it has violated the subjective terms of the validity of the agreement which also includes the material requirements of an authentic deed, namely the agreement of the parties. Thus, the Notary can prevent and overcome the cancellation of the deed if the Notary performs due diligence as stipulated in Article 16 paragraph (1) letter a UUJN. The notary can start examining documents from identifying the identity of the appearer, carefully verifying the subject and object data of the appearer, drawing up a deed with sufficient timeframe, fulfilling the formal and material requirements of the deed, reporting if there are indications of money laundering, expanding knowledge and professional expertise in accordance with the times, as well as conducting legal counseling for appearers.